Innovative Document Sterilization: Ultraviolet-C and Heating Approach for Effective Pathogen Elimination: Sterilisasi Dokumen yang Inovatif: Pendekatan Ultraviolet-C dan Pemanasan untuk Penghapusan Patogen yang Efektif - Akhmad Ahfas; Dwi Hadidjaja R.S; Agus Hayatal Falah (Universitas Muhammadiyah Sidoarjo, 2023)
In the context of the widespread transmission of Covid-19 via various mediums, including physical contact and contaminated surfaces, the critical need for document sterilization becomes apparent. Addressing this concern, a Document Sterilization Box was developed utilizing Ultraviolet-C (UV-C) Light and Heating methods, integrated with an Arduino Uno system equipped with LCD, LED displays, and a Buzzer for remote monitoring. The study aimed to assess the efficacy of this approach, achieving successful results with an average Lux reading of 204.6 and a temperature of 31.9 ̊C, within a 2-minute timeframe and humidity of 111.3%. The Document Sterilization Box employing UV-C Light and Heating proved to be a highly effective, safe, and environmentally friendly method, eliminating 100% of harmful microorganisms without causing damage to the exposed objects. This innovation offers valuable implications for enhancing hygiene practices and safeguarding public health on a global scale. Highlight: Emerging Necessity: Recognizing the critical need for effective document sterilization due to Covid-19 transmission via various mediums, including contaminated surfaces and physical contact. Technological Innovation: Introducing a Document Sterilization Box incorporating Ultraviolet-C Light and Heating methods, enhanced by Arduino Uno system, LCD, LED displays, and remote monitoring capabilities. Efficacy and Implications: Successfully achieving high efficacy in eliminating harmful microorganisms, the UV-C Light and Heating approach offers a safe, eco-friendly solution with global implications for elevating hygiene standards and preserving public health. Keyword: COVID-19 Transmission, Document Sterilization, Ultraviolet-C Light, Heating Method, Arduino Uno System